Goal-setting in physiotherapy: exploring a person-centered perspective - Melin, Jeanette; Nordin, Åsa; Feldthusen, Caroline; Danielsson, Louise (Physiotherapy theory and practice, 2021)
Objective: To analyze definitions and related requirements, processes, and operationalization of person-centered goal-setting in the physiotherapy research literature; to discuss those findings in relation to underlying principles of person-centeredness; and to provide an initial framework for how person-centered goal-setting could be conceptualized and operationalized in physiotherapy. Methods: A literature search was conducted in the databases: CINAHL, PubMed, PEDro, PsycINFO, REHABdata and Scopus. A content analysis was performed on how person-centered goal-setting was described. Results: A total of 21 articles were included in the content analysis. Five categories were identified: 1) Understanding goals that are meaningful to the patients; 2) Setting goals in collaboration; 3) Facing challenges with person-centered goal-setting; 4) Developing skills by experiences and education; and 5) Changing interaction and reflective practice. These categories were abstracted into two higher-ordered interlaced themes: 1) To seek mutual understanding of what is meaningful to the patient; and 2) To refine physiotherapy interaction skills, which we suggest would be useful for further conceptualization. Conclusion: In this analysis, we interpreted person-centered goal-setting in physiotherapy as a process of interaction toward a mutual understanding of what is meaningful to the patient. Future research may explore how to integrate mindful listening, embodied interaction and continuous ethical reflection with different assessments and treatment methods.